Factors Associated with the Occurrence of Hypertension in Pregnant Women - Yuni Sulistiawati (Bulletin of Inspiring Developments and Achievements in Midwifery, 2025)
Hypertension in pregnancy is a major cause of maternal and fetal morbidity and mortality, especially in developing countries. Various risk factors such as maternal age, parity, and obesity are thought to contribute to the incidence of gestational hypertension. Purpose: This study is a literature review study with an analytical approach. Methods: Data were obtained from 15 articles published between 2014–2020 and accessed through the PubMed, GARUDA, and Google Scholar databases. Inclusion criteria included publications discussing the relationship between age, parity, obesity, and gestational hypertension in full-text form. Results Most of the study results showed that pregnant women aged <20 years or >35 years had a higher risk of developing hypertension. Extreme parity (primiparity and multiparity ≥3) was also significantly associated with increased blood pressure during pregnancy. Obesity (BMI ≥27) was found to be a dominant risk factor, with a six-fold increase in the risk of hypertension. Implications: According to this study, antenatal care services should include screening for hypertension risk based on the age, parity, and nutritional condition of expectant mothers in order to more effectively and early prevent pregnancy problems. Conclusion : There is a significant relationship between age, parity, and obesity with the incidence of hypertension in pregnancy.